Factors influencing intention to use Islamic credit cards in Malaysia - Abdul Razak, Dzuljastri; Faris, Ammar; Shariff, Syazwan (2018)
The purpose of this study is to determine the main factors influencing the intention of consumers in Malaysia to use Islamic credit cards (ICC). It uses a survey methodology distributed to different categories of people and analysed via factor analysis, correlation and multiple regression analysis. The results indicated that religious motivation and ICC benefits contributed to the deciding factors influencing the intention to use ICC in Malaysia albeit the latter has a slighter greater impact. Fair pricing is not considered to be a factor. The findings imply that ICCs are perceived by many customers similar to conventional Credit Card. Hence more marketing efforts should be made to promote based on its Islamic values.